Performance of Semi Active Lateral Control (SALC) algorithm for semi active suspension system in multibody co-simulation method / M. M. Abdul Majid ...[et al.] - Abdul Majid, M. M.; Salleh, M. S.; Abu Hashim, M. A.; Ismail, N. H.; Mansor, S.; Abu Bakar, S. A. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
The publication presents a controller strategy used in development of Semi Active Lateral Control (SALC) algorithm for passenger vehicle in enhancing transient handling performance using multibody co-simulation approach. Most of research in semi active suspension are focusing on ride comfort performance instead of handling due to nature of damping definition as energy dissipation element. Thus limiting benefits on handling characteristic with current available algorithms. The research scope covered experimental measurements, simulation model correlation, and vehicle plant modelling using multibody approach (MSC Adams/Car), controller algorithm development in Matlab/Simulink and performance validation in co-simulation environment. The test vehicle was instrumented with Racelogic’s measurement tools for physical measurement on transient Step Steer manoeuvre. The experimental data used for simulation model correlation and validation. New controller algorithm (SALC) was than developed in Matlab/Simulink and integrate with correlated vehicle plant model for handling performance validation against passive suspension and Skyhook. The integration approach between MSC Adams/Car and Matlab/Simulink known as co-simulation or Software in the Loop (SiL), involve multiple solvers in one computational loop. In this research, the proposed SALC algorithm shows a significant improvement on transient handling (Step Steer), up to 21.8% in comparing to Skyhook performance. Thus led to the conclusion on additional benefits of semi active suspension system in handling performance beside ride comfort.